ANALISIS FAKTOR NON-LINGUISTIK PENGHAMBAT SISWA DALAM BERBICARA BAHASA INGGRIS PADA SISWA MTSS RAUDHATUL AKMAL BATANG KUIS - Mayadrie Aidhi Aridzki; Foury Widya Anjani; Syarifah Widya Ulfa (ALFIHRIS : Jurnal Inspirasi Pendidikan, 2023)
This study aims to determine the inhibiting factors of students in speaking English and to determine the teacher's perception of the inhibiting factors of students in speaking English as a foreign language. This was done to overcome students' problems in learning the target language and solve students' problems in learning to speak. Descriptive qualitative research was chosen as the research design in conducting this research. Besides that, it also involves students as the subject of this research. The results of the study show that two main factors, affective and cognitive factors, seem to hinder students in learning to speak English as a foreign language. In addition, students also get more influence from affective factors as the first main factor that hinders students in learning to speak English. The results of the study also show that teachers positively agree that the inhibiting factors as mentioned previously also hinder students in learning to speak English as a foreign language. In the end, the teacher must also consider the results of the research as a material consideration in designing activities in the learning process of speaking English as a foreign language that will help students to overcome their speaking problems.